Environmental determinants in sustaining the transmission of lymphatic filariasis: a systematic review - Ahmad Farid Nazmi Abdul Halim,; Shahrul Azhar Md Hanif,; Noor Adilla Md Anuar Hussain,; Aliff Faisal Ahmad Kamar,; Ahmed Alabed, Alabed Ali; Rahmat Dapari,; Mohd Rohaizat Hassan, (Universiti Kebangsaan Malaysia, 2025)
Since mass drug administration continues in many of the endemic countries, it is vital to synthesise evidence to adapt the challenges contributed by the environments. As such, the aim of this review was to explore relationship between lymphatic filariasis prevalence and potential environmental determinants. We searched the electronic databases PubMed, Web of Science, Cochrane, and Scopus between Jan 1, 2013, and Dec 31, 2022, for studies fulfilling the following criteria: it was an original article investigating the environmental determinants associated with transmission of lymphatic filariasis; and the study was published in English. The quality assessment tools for observational studies from the National Heart, Lung, and Blood Institute was used to assess the study quality. This systematic review was registered with the PROSPERO database (CRD42023393018). We identified 409 potentially eligible published articles, of which 11 met our inclusion criteria. The main environmental determinants associated with lymphatic filariasis transmission were Normalised Difference Vegetation Index (NDVI), land cover, distance to waterbody, rainfall/precipitation, elevation, slope, day land surface temperature, average annual temperature, house type and distance to stable light. This review is one of the steps towards understanding the associations between environmental determinants and transmission of lymphatic filariasis. These results can be used in future evidence-based strategies to strengthen surveillance and control strategies.